GlobalFungi, a global database of fungal occurrences from high-throughput-sequencing metabarcoding studies - Větrovský, Tomáš; Morais, Daniel; Kohout, Petr; Lepinay, Clémentine; Algora, Camelia; Awokunle Hollá, Sandra; Bahnmann, Barbara Doreen; Bílohnědá, Květa; Brabcová, Vendula; D'Alò, Federica; Human, Zander Rainier; Jomura, Mayuko; et al. (Scientific data, 2020)
Fungi are key players in vital ecosystem services, spanning carbon cycling, decomposition, symbiotic associations with cultivated and wild plants and pathogenicity. The high importance of fungi in ecosystem processes contrasts with the incompleteness of our understanding of the patterns of fungal biogeography and the environmental factors that drive those patterns. To reduce this gap of knowledge, we collected and validated data published on the composition of soil fungal communities in terrestrial environments including soil and plant-associated habitats and made them publicly accessible through a user interface at https://globalfungi.com . The GlobalFungi database contains over 600 million observations of fungal sequences across > 17 000 samples with geographical locations and additional metadata contained in 178 original studies with millions of unique nucleotide sequences (sequence variants) of the fungal internal transcribed spacers (ITS) 1 and 2 representing fungal species and genera. The study represents the most comprehensive atlas of global fungal distribution, and it is framed in such a way that third-party data addition is possible.
Keywords: houby; vysoce účinné nukleotidové sekvenování; rostliny; Soil Microbiology; mykobiom; Mycobiome; půdní mikrobiologie; DNA Barcoding, Taxonomic; High-Throughput Nucleotide Sequencing; Fungi; taxonomické DNA čárové kódování; Plants